Impact of faculty development programme on self-efficacy, competency and attitude towards medical education in Bhutan: a mixed-methods study - Tenzin, Karma; Dorji, Thinley; Choeda, Tshering; Pongpirul, Krit (BMC medical education, 2019)
Soon after Bhutan's first medical university was established in 2012, Faculty Development Programmes (FDPs) were adopted for efficient delivery of postgraduate medical curriculum. Medical education was an additional responsibility for the clinicians who already had multi-dimensional roles in the healthcare system where there is acute shortage of healthcare professionals. We studied the impact of FDPs on postgraduate medical education in Bhutan. This was a mixed-methods study with a quantitative (cohort study - quasi-experimental with 18 participants) and concurrent explanatory qualitative component (focused group discussion (FGD) with 11 teaching faculty members). The 18 participants were given a structured FDP designed by the University. The FGD assessed teacher self-efficacy and competency using standard tools before and after the FDP. Thematic analysis of the FGD explored the impact of FDPs in the delivery of postgraduate residency programmes. There were significant increase in the teacher self-efficacy (31 vs 34, p = 0.009) and competency scores (56 vs 64, p = 0.011). There were significant improvements in self-efficacy in the domain of the teaching relevant subject contents and developing creative ways to cope with system constraints. In teaching-learning assessments, there was a significant appreciation of the effectiveness of lectures and tutorials and the use of essay questions. The FGD demonstrated the acceptance of FDPs and its importance in quality improvement of postgraduate medical education, professional development of teachers and improvement of their communication skills. The teachers have now migrated from the conventional methods of teaching to workplace-based teaching and assessment. The FDPs also resulted in review and revision of postgraduate medical curriculum soon after the first batch graduated in 2018. Lack of adequate support from relevant stakeholders and lack of a medical education centre in the University were seen as major challenges. The FDPs have brought tangible professionalization of postgraduate medical education at an early stage of the medical university. There is a need for continued efforts to strengthen, sustain and consolidate the gains made thus far.